Comparative Effectiveness Of Organic Waste–Based Eco-Enzyme And Commercial Bio-Bacterial Agents In Railway Toilet Wastewater Treatment - Johannes Martua Hutagalung; Karina Marwahati; Lia Muliati; Usamah Rizqi Alfian; Retno Prasongko (Universitas Insan Cendekia Mandiri, 2026)
The growing number of railway passengers in Indonesia demands improved service quality, including the provision of environmentally friendly toilet facilities. The Railway Eco-Toilet (RET) system has adopted a waste storage mechanism to reduce direct discharge into tracks or water bodies. However, the stored wastewater still requires further treatment to meet environmental quality standards. One potential alternative is eco-enzyme, a fermentation product of household organic waste that contains enzymes, organic acids, and beneficial microorganisms capable of degrading pollutants. This study aims to analyze the performance of eco-enzyme in reducing pollutants in RET wastewater and to compare it with a commercial bio-bacteria product currently applied by PT KAI. The observed parameters include Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Dissolved Solids (TDS), and Total Suspended Solids (TSS). The experiment was conducted by directly applying eco-enzyme to RET storage tanks with incubation periods of 10, 15, and 20 days. Samples were then analyzed in an accredited laboratory using standard water quality testing methods. The results on the 20th day showed that eco-enzyme reduced pollutant levels to BOD5 of 70 mg/L, COD of 206 mg/L, TDS of 1478 mg/L, and TSS of 14 mg/L. In comparison, the commercial bio-bacteria achieved BOD5 of 63 mg/L, COD of 204 mg/L, TDS of 1129 mg/L, and TSS of 53 mg/L. The analysis indicated that eco-enzyme performed better in reducing TSS, achieving compliance with environmental standards, whereas both treatments failed to lower BOD5 and COD to the required limits. These findings highlight the potential of eco-enzyme as an alternative for treating railway toilet wastewater. Its application could strengthen RET systems and be extended to domestic wastewater management such as household septic tanks.